Evaluating the Guo–Campanella viscoelastic model - Augusto P.E.D. (2018)
The authors are grateful to the National Council for Scientific andTechnological Development (CNPq, Brazil) for funding the project n8401004/2014–7 and Cienciactiva from the“Consejo Nacional deCiencia, Tecnología e Inovaci on Tecnol ogica”(CONCYTEC, Peru) forthe A.C. Miano (Contract 272–2015-FONDECYT) and M.L. Rojas(Contract 087–2016-FONDECYT) Ph.D. scholarships.